Presentation N° 11 (2023) - Castro, Augusto (2023)
We are pleased to present another issue of Revista Kawsaypacha: Sociedad y Medio Ambiente, a journal of the Institute of Nature, Earth, and Energy at the Pontificia Pontifical Catholic University of Peru (INTE-PUCP). In this 11th issue, several important contributions are gathered, allowing us to contribute to a better understanding of socio-environmental subjects.